Nevus depigmentosus. - Pontillo, A.; Farro, P.; Di Girolamo, F.; De Roma, M.R.; Conca, R.; Berloco, A.; Bonifazi, E. (European Journal of Pediatric Dermatology, 2000)
Nevus depigmentosus (ND) was first reported by Lesser in 1884 (13). Present at birth or from the first years, ND is a nevus malformation persisting indefinitely. Although not yet clarified from a pathogenetic point of view, ND is well defined from a clinical point of view and characterized by a decreased pigmentation as compared with the healthy surrounding skin. Its pigmentation is decreased, but not lacking, as shown by its color, which is less light as compared with the color of vitiligo and piebaldism, and by the possibility of getting tanned.